BUMDES IMPROVEMENT STRATEGY IN THE COMMUNITY ECONOMY IN LAMATTI RIATTANG VILLAGE - Arnida; Zulkifli Arifin; Nor Syahira; Mohd. Raswan (Jurnal Ilmiah Administrasita', 2024)
The implementation of BUMDes has not been fully implemented by all villages in Indonesia Until the issuance of Law Number 6 of 2014. Even in its implementation in several regions, the existence of BUMDes has not been able to run effectively and is able to contribute to the development and empowerment of communities in these villages. This study intends to find out the pattern of utilization of BUMDes funds by taking a case study in Lamatti Rattang Village, Bulupoddo District, Sinjai Regency, which is one of the villages implementing BUMDes. Broadly speaking, the aims of this research are first, to find out the role of BUMDes for the community, secondly, to find out the implementation of BUMDes and the third, to find out the supporting and inhibiting factors of BUMDes. This study used a qualitative approach with in-depth interviews with the Lamatti Riattang BUMDes manager and community members involved in BUMDes activities. The data obtained was analyzed descriptively to understand the management practices and impacts of empowering BUMDes in the village of Lamatti Riattang. This research shows that the empowerment of BUMDes in Lamatti Riattang Village has not been maximized but can have a positive impact on improving the village economy and community welfare. BUMDes can be a relevant model for local economic development in other villages. BUMDes Lamatti Riattang needs government support, good cooperation between BUMDes and the community, and effective management to ensure the sustainability and success of BUMDes in the long term.